Dinamika Agama, Pendidikan, Sosial dan Budaya Masyarakat Urban di Madura - Mo'tasim, Mo'tasim; Fauzi, Muhammad (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2023)
Social and cultural changes that occur in urban society have resulted in a shift in religious values, where religion is only used as symbols of self-identity. This behavior pattern tends to lead to the formation of self-imitation. This results in social inequalities and changes in religious, social and cultural values. This research tries to analyze the religious, social and cultural changes that have occurred in the community of Sukolilo Village, Labang District, Bangkalan Regency, which have had a lot of influence on their life patterns. This research uses a phenomenological approach. Meanwhile, this type of research is descriptive research. The results of the research show that the dynamics of religion lead to the mosque being a place of worship for Muslims. Apart from being a center for religious activities, the mosque is also a center for social activities. Social dynamics show that the level of education in Sukolilo Bangkalan is relatively low, with minimal children continuing their education to high school level. Community employment, namely work in the service and informal sectors. Meanwhile, in the cultural aspect, the language used by the majority of people is Madurese which is very dominantly used as a means of communication in their daily activities in their environment with some mixture of Javanese language originating from Surabaya. The author argues that this dynamic becomes a social inevitability amidst the intersection of several aspects above, which coincides with the roar of information "spillover" in society